2019
DOI: 10.1053/j.jfas.2018.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopically Assisted Anterior Treatment of Symptomatic Large Talar Bone Cyst

Abstract: Symptomatic cystic lesions of the talus are rare. The traditional operations usually do not provide visualization to reveal the deep structure of the lesion and could cause cartilage damage or other severe traumatic injury. We report an operative technique to reach the cystic lesion without talar cartilage damage, remove the lesion, and fill defect with a bone graft assisted by anterior arthroscopy and evaluate its safety and reliability for future study. Seven cases of talar bone cyst were included. The patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…This technique is especially suitable for bone cysts combined with other structural abnormalities at the posterior malleolus, such as tenosynovitis of flexor pollicis longus, symptomatic triquetral bone, and villonodular synovitis. Zhu et al reported an anterior arthroscopic treatment for 7 cases of talar bone cysts, which also achieved satisfactory results in the short term [5]. In this study, the number of cases has been increased to 21; as for the location of cysts, in addition to the talus, distal tibia and calcaneus were also included.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This technique is especially suitable for bone cysts combined with other structural abnormalities at the posterior malleolus, such as tenosynovitis of flexor pollicis longus, symptomatic triquetral bone, and villonodular synovitis. Zhu et al reported an anterior arthroscopic treatment for 7 cases of talar bone cysts, which also achieved satisfactory results in the short term [5]. In this study, the number of cases has been increased to 21; as for the location of cysts, in addition to the talus, distal tibia and calcaneus were also included.…”
Section: Discussionmentioning
confidence: 98%
“…For example, the incidence of talar bone cysts accounts for 0.003% of the bone tumor, and they are commonly diagnosed as simple bone cysts, aneurysmal bone cysts, intraosseous ganglion, etc. [1][2][3][4][5][6][7][8]. The etiology and mechanism of bone cysts have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…However, when the talus is extensively destroyed, there is risk of pathologic fracture and damage to the articular cartilage, leading to persistent swelling and pain of the subtalar joint and ankle joint. 3 For symptomatic cyst recalcitrant to conservative treatment, surgery is indicated. Because most of the area of the talus is covered with articular cartilage, it is rather difficult to conduct surgical procedures without damaging the cartilage of the talus.…”
mentioning
confidence: 99%
“…Because most of the area of the talus is covered with articular cartilage, it is rather difficult to conduct surgical procedures without damaging the cartilage of the talus. 3 Open debridement and bone grafting frequently requires extensive soft-tissue dissection or even different types of malleolar osteotomy for proper access to the lesion. 3 , 4 Arthroscopic treatment is a possible solution to reduce the surgical trauma and eliminate the need of osteotomy.…”
mentioning
confidence: 99%
See 1 more Smart Citation